1994
DOI: 10.1177/1073191194001002003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neuropsychological Test Performance in PTSD, Generalized Anxiety Disorder, and Control Vietnam Veterans

Abstract: Although impairment in cognitive functioning is theoretically linked to the presence of post-traumatic stress disorder (PTSD), the actual impact of this disorder on neuropsychological performance remains largely unknown. While a modest amount of empirical attention has been directed toward examining the neuropsychological correlates of PTSD, several methodological problems, most notably small sample sizes and the resulting lack of power, have greatly restricted generalizability of findings. The present study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
4
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 16 publications
4
44
4
1
Order By: Relevance
“…Poor use of encoding strategies and reduced levels of organization have also been found (Veiel, 1997). Studies on PTSD samples that have included clinical comparison samples have found less clear patterns of PTSD-specific impairment (Gil, Calev, Greenberg, Kugelmass, & Lerer, 1990;Zalewski, Thompson, & Gottesman, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Poor use of encoding strategies and reduced levels of organization have also been found (Veiel, 1997). Studies on PTSD samples that have included clinical comparison samples have found less clear patterns of PTSD-specific impairment (Gil, Calev, Greenberg, Kugelmass, & Lerer, 1990;Zalewski, Thompson, & Gottesman, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…A careful review of the literature demonstrated that the three studies of cognition conducted to date with the largest sample sizes have yielded negative findings (Barrett, Green, Morris, Giles, & Croft, 1996;Crowell et al, 2002;Zalewski, Thompson, & Gottesman, 1994). The study by Barrett is particularly noteworthy because they found that veterans with PTSD alone (N = 236) did not show lower scores on measures of cognitive functioning compared to normal comparison participants (N = 1,835), whereas veterans with both PTSD and a concurrent diagnosis of depression, another anxiety disorder, or substance abuse (N = 128) performed significantly less well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving sleep, prazosin may improve cognitive function by reducing the anxiety associated with PTSD. Subjects with PTSD have impaired cognitive function that can be attributed in part to anxiety [20]. Prazosin may reduce anxiety in veterans with PTSD by reducing central nervous system noradrenergic activity [21].…”
Section: Traumatic Brain Injury (Tbi) Is An Important Health Issue Fomentioning
confidence: 99%